Indentation fracture toughness of Aluminium-Graphite composites: influence of nano-particles - Alqahtani Ibrahim; B. Niyaz Ahmed; E. Ashoka; A. M. Rajesh; P. B. Bharath; Doddamani Saleemsab (Fracture and Structural Integrity)
n the field of composite materials, extensive research has been undertaken on aluminum-graphite composites. However, a research gap has been identified regarding the specific influence of nano-sized graphite particles on their fracture toughness. Previous studies have predominantly focused on larger graphite particles or different reinforcement materials, resulting in relatively unexplored effects of nano-graphite particles. This research is deemed critical as it has the potential to generate lightweight, high-strength materials, aligning with the demands of aerospace, automotive, and structural engineering. The primary objective of this study is to investigate how the inclusion of nano-sized graphite particles affects the fracture toughness of aluminum-graphite composites. To achieve this objective, systematic dispersion and incorporation of nano-sized graphite particles into an aluminum matrix will be carried out. Mechanical testing, including fracture toughness assessments, will be conducted to evaluate the performance of the composite materials. Factors such as particle size, distribution, volume fraction, and interfacial bonding will also be characterized within the study. It is anticipated that the presence of nano-sized graphite particles will lead to a significant enhancement of the fracture toughness of the aluminum-graphite nanocomposites. This enhancement is expected to be attributed to crack deflection, tortuosity, altered stress distribution, and increased plastic deformation around cracks